To solve for x, you need to isolate/get the variable "x" by itself in the equation.
5x + 5 = 3x + 4 Subtract 3x on both sides to get "x" on one side of the equation
5x + 5 - 3x = 3x + 4 - 3x
2x + 5 = 4 Subtract 5 on both sides
2x + 5 - 5 = 4 - 5
2x = -1 Divide by 2 on both sides to get "x" by itself
![(2x)/(2) =(-1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/7wkfefi4htceh5ctqjexm7gc9clnyucmdj.png)
![x = -(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/rxmu0mq745ej22uhrey0ubf0fkk013azwb.png)